OP0193 BIIB059, A HUMANIZED MONOCLONAL ANTIBODY TARGETING BDCA2 ON PLASMACYTOID DENDRITIC CELLS (PDC), SHOWS DOSE-RELATED EFFICACY IN THE PHASE 2 LILAC STUDY IN PATIENTS (PTS) WITH ACTIVE CUTANEOUS LUPUS ERYTHEMATOSUS (CLE). (2nd June 2020) - Werth, V.; Furie, R.; Romero-Diaz, J.; Navarra, S.; Kalunian, K.; Van Vollenhoven, R.; Nyberg, F.; Kaffenberger, B.; Sheikh, S.; Radunovic, G.; Huang, X.; Carroll, H.; et al.
Abstract : Background: CLE represents an unmet medical need with no approved therapy. BIIB059, a humanized monoclonal antibody, binds to BDCA2 and inhibits pro-inflammatory mediators production, including type I interferons. BIIB059 was evaluated in Phase 1 studies NCT02106897 and NCT03224793 . LILAC is a 2-part Phase 2 study: Part A enrolled SLE pts; Part B enrolled pts with active CLE (NCT02847598 ). Objectives: Evaluate efficacy and safety of BIIB059 in pts enrolled in Part B at Week 16, end of treatment (EOT) period. Methods: Pts with active CLE, SCLE and/or CCLE and adjudicated Cutaneous Lupus Disease Area and Severity Index – Activity (CLASI-A) ≥8 were enrolled and randomized to receive either BIIB059 (50, 150 or 450 mg) or placebo (PBO) s.c. Q4W. Primary endpoint was dose response defined by % change in CLASI-A score from baseline (BL) to Week 16. Secondary endpoints included CLASI-50 response rate and ≥ 7-point reduction in CLASI-A score from baseline to EOT. Adverse events and serious adverse events were recorded throughout the study. Results: 132 pts with active CLE were randomized. The study met its primary endpoint, demonstrating a dose response (p= 0.0005) and a statistically significant difference in % change from BL in CLASI-A score in BIIB059-treated pts vs PBO. Table 1 and Table 2 summarize efficacy and safety results, respectively. Conclusion: BIIB059 administration to pts with active CLE resulted in statistically significant dose-related improvement in disease activity vs PBO with no untoward safety signals. Further development of BIIB059 in CLE is warranted. Disclosure of Interests: Victoria Werth Grant/research support from: Biogen, Celgene, Gilead, Janssen, Viela, Consultant of: Biogen, Gilead, Janssen, Abbvie, GSK, Resolve, AstraZeneca, Amgen, Eli Lilly, EMD Serono, BMS, Viela, Kyowa Kirin, Richard Furie Grant/research support from: AstraZeneca, Biogen, Consultant of: AstraZeneca, Biogen, Juanita Romero-Diaz Consultant of: Biogen, Sandra Navarra Speakers bureau: Astellas, Novartis, Pfizer, Johnson & Johnson, Abbvie, Kenneth Kalunian Grant/research support from: Pfizer, Lupus Research Alliance, Sanford Consortium, Consultant of: Genentech, Nektar, BMS, Janssen, AstraZeneca, Biogen, Vielabio, Equillium, Eli Lilly, ILTOO, Abbvie, Amgen, Roche, Gilead, Ronald van Vollenhoven Grant/research support from: AbbVie, Arthrogen, Bristol-Myers Squibb, GlaxoSmithKline, Lilly, Pfizer, and UCB, Consultant of: AbbVie, AstraZeneca, Biotest, Bristol-Myers Squibb, Celgene, GSK, Janssen, Lilly, Medac, Merck, Novartis, Pfizer, Roche, and UCB, Filippa Nyberg Consultant of: Biogen, Benjamin Kaffenberger Grant/research support from: Amgen, Biogen, InflaRx, Veloce Biopharmaceuticals, Dermatology Foundation, Saira Sheikh: None declared, Goran Radunovic: None declared, XIAOBI HUANG Shareholder of: Biogen, Employee of: Biogen, HUA CARROLL Shareholder of: Biogen, Employee of: Biogen, Francois Gaudreault Shareholder of: Biogen, Employee of: Biogen, Adam Meyers Shareholder of: Biogen, Employee of: Biogen, Catherine Barbey Shareholder of: Biogen, Employee of: Biogen, Cristina Musselli Shareholder of: Biogen, Employee of: Biogen, NATHALIE FRANCHIMONT Shareholder of: Biogen, Employee of: Biogen